Ezekiel Current Debates and Future Directions - Tooman, William A.; Barter, Penelope (Mohr Siebeck, 2017)
Ezechiel. Aktuelle Debatten und zukünftige Ausrichtungen.
PublicationDate: 20170512
Keywords: Hebrew Bible -- Old Testament -- Prophets -- Altes Testament -- Antike -- Array